Sexual harassment & sexual consent - Dank, Barry M.; Refinetti, Roberto (Transaction Publishers, 1998)
Sexual Harassment and Sexual Consent serves as a compelling forum for the analysis of ethical, cultural, social, and political issues related to sexual relationships and sexual behavior. These issues include, but are not limited to: sexual consent and sexual responsibility; sexual harassment and freedom of speech and association; sexual privacy; censorship and pornography; impact of film/literature on sexual relationships; and university and governmental regulation of intimate relationships.The premier volume deals with a central theme: sexual harassment and sexual consent, with emphasis on academia. Theoretical articles, research reports, editorials, and book reviews analyze issues from psychological, sociological, political, and artistic perspectives. Contributions include: "Eight Reasons Not to Prohibit Relationships between Professors and Students" by Peg Tittle; "The Impact of Sexual Misconduct on the Reputation of Martin Luther King, Jr." by A. B. Assensoh and Y. Alex-Assensoh; "Homosexuality, Sexual Harassment, and Military Readiness" by Deborah E. Kapp and Gary A. Kustis; " and "College Students' Perceptions of the Relationship between Sex and Drinking" by Gwendell W. Gravitt, Jr., and Mary M. Krueger.Also included are reviews of Sexual Harassment on Campus edited by B. R. Sandler and R. J. Shoop; Making Gender: The Politics and Erotics of Culture by S. B. Ortner; The Power of Beauty by N. Friday; Bound and Gagged: Pornography and the Politics of Fantasy in America by L. Kipnis; and Mediated Sex by B. McNair. In addition, Warren Farrell reviews the film First Wives Club. This initial volume of Sexuality and Culture will be of interest to all those who participate in campus life as well as sociologists, psychologists, and government and university policymakers.